2008
DOI: 10.1103/physrevb.78.094413
|View full text |Cite
|
Sign up to set email alerts
|

Critical thickness and orbital ordering in ultrathinLa0.7Sr0.3MnO3films

Abstract: Detailed analysis of transport, magnetism, and x-ray absorption spectroscopy measurements on ultrathin La 0.7 Sr 0.3 MnO 3 films with thicknesses from 3 to 70 unit cells resulted in the identification of a lower critical thickness for a nonmetallic nonferromagnetic layer at the interface with the SrTiO 3 ͑001͒ substrate of only three unit cells ͑ϳ12 Å͒. Furthermore, linear-dichroism measurements demonstrate the presence of a preferred ͑x 2 -y 2 ͒ in-plane orbital ordering for all layer thicknesses without any … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

33
312
2

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 405 publications
(347 citation statements)
references
References 50 publications
33
312
2
Order By: Relevance
“…Tensile (compressive) strain modifies the crystal field so as to favor the in-plane orbital d x 2 −y 2 (out-of-plane orbital d 3z 2 −r 2 ). 9,10 However, utilizing strain is a static approach to tailoring the desired orbital configuration. 21 In this Letter, we describe an approach that utilizes nanoscale ferroelectrics and enables reversibly modulating orbital occupations at La 1−x Sr x MnO 3 (LSMO, x=0.2 for the current study) interfaces.…”
mentioning
confidence: 99%
“…Tensile (compressive) strain modifies the crystal field so as to favor the in-plane orbital d x 2 −y 2 (out-of-plane orbital d 3z 2 −r 2 ). 9,10 However, utilizing strain is a static approach to tailoring the desired orbital configuration. 21 In this Letter, we describe an approach that utilizes nanoscale ferroelectrics and enables reversibly modulating orbital occupations at La 1−x Sr x MnO 3 (LSMO, x=0.2 for the current study) interfaces.…”
mentioning
confidence: 99%
“…11). Observed interfacial dead layers have, however, limited the scaling of potential devices [12][13][14] . While explicit attempts 15,16 to offset the interface dipole 17,18 and to eliminate extrinsic defects 14 have reduced the observed dead layer thickness, direct mapping of these intrinsic electronic and magnetic reconstructions at the interface can be obscured by variations in growth techniques leading to competing defects.…”
mentioning
confidence: 99%
“…In the La 1-x Sr x MnO 3 solid solution, the electron occupancy of the e g doublet depends on the strength of the JahnTeller distortion, which in turn is determined by the hole doping level, x (Tokura and Nagaosa, 2000). In epitaxial thin films, however, similarly to the Jahn-Teller distortion, misfit strains have the ability to break the x 2 − y 2 /3z 2 − r 2 orbital degeneracy (Fang et al, 2000) as recently confirmed by X-ray linear dichroism investigations (Huijben et al, 2008;Tebano et al, 2008;Pesquera et al, 2012). A thorough investigation taking into account the attenuation of the signal with the depth in the sample, suggests that the observed X-ray linear dichroism is rather a consequence of the superposition of interfacial and free surface effects (Pesquera et al, 2012).…”
Section: Misfit Strainmentioning
confidence: 80%